The newspaper in language class (Journal of Parents and Teachers, 2026)
The EALRC method (Exploration, Self-questioning, Reading, Summarising, Checking) could well be regarded as the approach generally adopted when reading and seeking to learn from what is read. Accordingly, the proposal here is to apply this method to newspaper reading, so as to address the objectives set out in the Basic Curriculum Framework for Language and Literature, in both primary and secondary education. The newspaper provides information and culture, whilst promoting values and norms for human and social development.
Keywords: newspaper; Laguage and Literature; EALRC Method; values